The effect of virtual reality laboratory on conceptual understanding in electrolytes and non-electrolytes - Afsari Amiati (Journal of Education and Learning (EduLearn), 2019)
This study aims to determine the effect of the use of learning media Virtual Reality Laboratory (VR-Lab) on the conceptual understanding of Senior high school students on the concept of electrolytes and non-electrolytes. The learning media used were developed using models adapted from the ADDIE model, while the type of research as a whole uses this type of research, namely Quasy experiment with posttest only design. The instrument used in this study was a multiple choice question of 40 items. This research was conducted using 84 students consisting of the control class, experiment I, and experiment II. The analysis technique used one-way ANOVA. The results obtained in this study were that between the control class and experiment I class there were no significant differences with a mean of 44.91 and 45.67. Whereas for the experimental II class had a significant difference with the other two classes with an average of 68.66.